Metabolic activity, reproduction and survival of the high littoral fringe copepod Itunella muelleri (Harpacticoida: Canthocamptidae) at different combinations of salinities and temperatures. - Steinarsdottir, M. & A. Ingolfsson (Journal of Crustacean Biology, 2011)
Survival, metabolic and reproductive activity of Itunella muelleri was tested in several combinations of temperatures (2u-30uC) and salinities (from fresh water to salinity of 34%). Proportions of individuals alive after 18 or 22 days was high in all experimental combinations except in fresh water at 2uC and at 30uC at salinities of 4 and 16%. Metabolic activity, as measured by the production of faecal pellets, was low in fresh water regardless of temperature. Metabolic activity was also very low at 2uC regardless of salinity. Maximum activity was found at 20uC and 22uC with little difference between salinities of 4, 8, 16, and 32%. Production of nauplii during the first 29 days was nil in fresh water regardless of temperature, and also nil at 2uC and 30uC regardless of salinities. The maximum production was found in the combination of 22uC and salinity of 16%. The results are discussed in relation to expected ambient conditions in the natural habitat of the species. KEY WORDS: Copepoda, Ice Itunella muelleri, littoral fringe, salinity tolerance, temperature tolerance